2018
DOI: 10.1149/2.0501815jes
|View full text |Cite
|
Sign up to set email alerts
|

CO2Electrolysis to CO and O2at High Selectivity, Stability and Efficiency Using Sustainion Membranes

Abstract: Carbon dioxide (CO 2 ) electrolysis provides a pathway to close the anthropogenic carbon cycle and store renewable energy, but the stability, selectivity, efficiency and rate of such process needs to be improved. In this paper, we explore the use of Sustainion imidazolium-functionalized membranes and ionomers to improve the performance of that process. Potentiometric runs at a fixed current of 200 mA/cm 2 using Sustainion membranes and ionomers showed that one can maintain 98% selectivity at about 3V applied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
243
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(258 citation statements)
references
References 47 publications
9
243
2
4
Order By: Relevance
“…The ratio of polymer to silver was 20%. This differs from values suggested in literature, [ 33,34 ] in an unsuccessful effort to maximize the visibility of the ionomer in the reconstruction. The GDE being specifically prepared for a tomographic study; it was not optimized for performance.…”
Section: Methodscontrasting
confidence: 76%
“…The ratio of polymer to silver was 20%. This differs from values suggested in literature, [ 33,34 ] in an unsuccessful effort to maximize the visibility of the ionomer in the reconstruction. The GDE being specifically prepared for a tomographic study; it was not optimized for performance.…”
Section: Methodscontrasting
confidence: 76%
“…We employed the electrochemical reduction of CO 2 to CO on Ag as a model reaction owing to its high selectivity, gaseous reactants/products, and robustness across multiple catalysts and cell configurations . We evaluated catalyst‐coated Freudenberg GDLs in a custom‐built, gas‐fed electrolyzer with a flowing electrolyte (Figure ).…”
Section: Resultsmentioning
confidence: 80%
“…In this configuration, the higher diffusivity of gaseous CO 2 (≈10 −1 cm 2 s −1 ) and the reduced diffusion lengths within the CL enable increased current densities, typically an order of magnitude or greater over atmospheric aqueous‐phase cell designs . Indeed, gas‐fed devices have demonstrated high geometric‐area‐specific current densities with a variety of CO‐ and hydrocarbon‐selective metal electrocatalysts . However, most emerging gas‐fed CO 2 electrolyzers often exhibit limited durability, with performance decay after only a few hours of operation, in part because these cell formats employ GDEs based on repurposed polymer electrolyte fuel cell (PEFC) materials that are not tailored to electrolysis applications.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, noble metals nanoparticles supported on carbon black are the catalysts of the most advanced electrolysers for gas-phase electro-reduction approaching a pilot demonstration phase [17,32,33]. Novel nanocarbon materials show in general modest results in terms of productivity.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Potentiometric electrolysis in gas phase at a fixed current of 200 mAcm −2 showed that 98% selectivity could be maintained at about 3 V voltage for five months, with a voltage increase of only 3 µV/hour. The improved performance was attributed to the extended three phase boundaries in Ag cathode [33]. These orders of magnitude of current densities are already meaningful for industrial deployment.…”
Section: Introductionmentioning
confidence: 95%